Study of effects of Sudarshan Kriya on Postmenopausal symptoms among central India women population : A preliminary study - Rajeshree Tukaram Patil (Asian Journal of Medical Sciences, 2017)
Background: Menopausal health concerns mainly include the vasomotor symptoms, cardiovascular symptoms, osteoporosis, cancer, sexual problems and urogenital atrophy. Our life style today leads to a lot of stress, depression and anxiety. Prolonged stress can make one experience the symptoms like menopause (though not actually inducing it). Yoga exercise meditation and life style modification have relieved stress and enhanced the quality of life. Sudarshan Kriya (SK) is a rhythmic breathing technique with 4 breath components. It has varied effects on body especially acting by relief of stress.